2004
DOI: 10.1071/ea03030
|View full text |Cite
|
Sign up to set email alerts
|

Limitations to pasture and sheep enterprises and options for improvement in the Victorian Mallee

Abstract: A survey of 29 sheep producers was conducted to benchmark current sheep production practices and producer attitudes to sheep and pasture management in the Victorian Mallee. This report describes the farming systems, defines current sheep management practices and identifies management issues that are limiting production. It also highlights limitations of adoption, suggests potential adoption rates of specific practices by producers, and estimates increases in productivity achievable. Sheep producers could achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…This suggested the concept of a central learning farm combined with network activities and providing the opportunity for producer input were concepts that received strong support across the New England region. This is consistent with the findings of Robertson and Wimalasuriya (2004) who conducted a survey of 29 sheep producers in the Victorian Mallee region to identify current issues with sheep and pasture management and constraints to adoption. They concluded that, to increase rates of adoption, there was a need for the collection of more data and benchmarking of both livestock and pastures within grazing enterprises in order to be better able to demonstrate the link between the production data and farm profit.…”
Section: Discussionsupporting
confidence: 67%
“…This suggested the concept of a central learning farm combined with network activities and providing the opportunity for producer input were concepts that received strong support across the New England region. This is consistent with the findings of Robertson and Wimalasuriya (2004) who conducted a survey of 29 sheep producers in the Victorian Mallee region to identify current issues with sheep and pasture management and constraints to adoption. They concluded that, to increase rates of adoption, there was a need for the collection of more data and benchmarking of both livestock and pastures within grazing enterprises in order to be better able to demonstrate the link between the production data and farm profit.…”
Section: Discussionsupporting
confidence: 67%
“…Many modelling studies have shown that increased climate variability decreases the number of livestock that can be managed per unit of land (Olson and Mikesell, 1988;Kingwell et al, 1993;Kobayashi et al, 2007). This modelling is supported by surveys of farmers, which suggest that most Australian farmers manage the stocking system at a fixed, manageable number of ewes to avoid having too many sheep in years with low pasture growth (Doyle et al, 1993;Austen et al, 2002;Robertson and Wimalasuriya, 2004). Therefore, regions with more reliable pasture growth should be able to manage sheep at a higher stocking rate, which may affect the value of traits in different regions.…”
Section: Introductionmentioning
confidence: 96%
“…There is a lack of quantitative information on the production of pastures and their impact on sheep production on farms for the Victorian Mallee, a low-rainfall (275mm to 375mm) mixed farming region. This has restricted attempts to define the impact of various management strategies on the production and profitability of sheep (Robertson and Wimalasuriya 2004). Reported data are largely restricted to experiments conducted over a limited number of years and pastures, with limited detail of both sheep and pasture production.…”
Section: Introductionmentioning
confidence: 99%
“…Latta (2003) is the only report describing both sheep and pasture production, but neither the stocking rates nor the improved pasture reflected common industry practice. The few reports from commercial properties do not provide detailed descriptions of both sheep and pasture production (Molnar 1962; Rigby and Latta 1995; Robertson and Wimalasuriya 2004).…”
Section: Introductionmentioning
confidence: 99%